Challenges in tackling tuberculosis on the Thai-Myanmar border: findings from a qualitative study with health professionals. Issue 1 (June 2015) - Kaji, Aiko; Thi, Sein; Smith, Terrence; Charunwatthana, Prakaykaew; Nosten, Francois
Abstract Background Myanmar and Thailand belong to the top 22 high burden countries for tuberculosis (TB). Health care organizations play an essential role in addressing TB control in the two bridging border jurisdictions, Tak province, Thailand and Myawaddy district, Kayin state, Myanmar. However, health professionals face difficulties in TB control effort due to the nature of fluid population movements, resource constraints and ambiguous mechanisms to implement collaboration along the border. The purpose of this study is to identify the challenges to TB control among Myanmar migrants faced by stakeholders, focusing on the area of collaboration and interaction along the border. Method The study conducted in-depth interviews with health policy makers and health care providers responsible for developing and implementing policies and TB programs in Tak province, Thailand and Myawaddy district, Kayin state, Myanmar. The participants included members of government organizations, United Nations agencies, community based organizations, and international NGO. One or two key stakeholders from each organization were approached to participate in the study. We gathered baseline information to identify TB policies and programs available on websites, brochures, and publications. Observations including field notes were made on site. The data transcriptions were coded for qualitative data analysis. Coding also developed categories that led to key themes. Results A total of 31 respondents (18 in Thailand and 13 in Myanmar) participated in the study. The main theme reported by participants was challenges in limited corroboration and coordination among stakeholders. Unstructured information sharing and lack of communication hindered the stakeholders from engaging in TB control. The respondents stressed that referral mechanisms across the border need to be strengthened. Other challenges were associated with increasing loss to follow up and subsequent MDR cases, constraints of service delivery, shortage of human resources, limited staff capacities within organizations and poor socioeconomic status of patients. Conclusions Health professionals face many challenges in effectively addressing TB control. Addressing the insufficient coordination and collaboration by strengthening bi-national collaborative mechanisms among health care organizations is an essential step in reducing the burden of disease. Additional support and resources from governmental and non-governmental agencies will be required to address the challenges.